Current and prospective therapeutic strategies: tackling Candida albicans and Streptococcus mutans cross-kingdom biofilm - Li, Yijun; Huang, Shan; Du, Jingyun; Wu, Minjing; Huang, Xiaojing (Frontiers in Cellular and Infection Microbiology, 2023)
Candida albicans (C. albicans) is the most frequent strain associated with cross-kingdom infections in the oral cavity. Clinical evidence shows the co-existence of Streptococcus mutans (S. mutans) and C. albicans in the carious lesions especially in children with early childhood caries (ECC) and demonstrates the close interaction between them. During the interaction, both S. mutans and C. albicans have evolved a complex network of regulatory mechanisms to boost cariogenic virulence and modulate tolerance upon stress changes in the external environment. The intricate relationship and unpredictable consequences pose great therapeutic challenges in clinics, which indicate the demand for de novo emergence of potential antimicrobial therapy with multi-targets or combinatorial therapies. In this article, we present an overview of the clinical significance, and cooperative network of the cross-kingdom interaction between S. mutans and C. albicans. Furthermore, we also summarize the current strategies for targeting cross-kingdom biofilm.